2023
DOI: 10.1371/journal.pntd.0011128
|View full text |Cite
|
Sign up to set email alerts
|

PCR for detection of Leishmania donovani from microscopically negative tissue smears of suspected patients in Gondar, Ethiopia

Abstract: Background As untreated visceral leishmaniasis (VL) is fatal, reliable diagnostics are pivotal for accurate treatment allocation. The current diagnostic algorithm for VL in Ethiopia, which is based on the rK39 rapid diagnostic test and microscopy of tissue smears, lacks sensitivity. This probably leads to missed cases and patients not receiving treatment. Methodology We conducted a retrospective study on stored microscopically negative spleen and bone marrow smears from suspected VL patients collected at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Previous research has consistently indicated that this method exhibits a notably low and variable sensitivity. Our findings were in agreement with these previous reports [49,58], revealing that the sensitivity of the microscopic examination of Giemsa-stained tissue aspirates is lower than any of the other five tests.…”
Section: Discussionsupporting
confidence: 94%
“…Previous research has consistently indicated that this method exhibits a notably low and variable sensitivity. Our findings were in agreement with these previous reports [49,58], revealing that the sensitivity of the microscopic examination of Giemsa-stained tissue aspirates is lower than any of the other five tests.…”
Section: Discussionsupporting
confidence: 94%
“…Notably, previous research has consistently indicated that this method exhibits a notably low and variable sensitivity. Our findings were in agreement with the previous reports [49,59], revealing that the sensitivity of microscopic examination of Giemsastained tissue aspirates is lower than any of the five tests.…”
Section: Discussionsupporting
confidence: 94%